Biomarkers for Early Detection of Ovarian Cancer: A Review - Gari Bindu, Devarajappa; Nanda Kumar, Kopparapu Venkata; Likitha Reddy, Kasireddy; Siva Charani, Mekala; Gowthami, Yaraganti (Asian Pacific Journal of Cancer Biology, 2024)
Ovarian cancer, with its asymptomatic early stages, poses a significant challenge for early diagnosis and survival improvement. The utilization of tumor markers, including CA -125 and HE4 has become crucial in detecting these silent killers. Additionally, gene-based markers like BRCA1 and BRCA2 mutations are increasingly acknowledged for indicating ovarian cancer susceptibility. Promising emerging biomarkers, such as microRNAs and circulating tumor cells, offer new research avenues and diagnostic possibilities for the early detection of ovarian cancer. This article provides a comprehensive review of current specific markers, gene-based indicators, emerging markers, and other notable approaches in the early identification of ovarian cancer.